الإدارة الإلكترونية بين مقتضيات الشفافية وإشكالية التخلص من البيروقراطية في الأجهزة الحكومية - إسماعيل, سايحي; المكي, دراجي (جامعة الوادي.University eloued, 2021)
تواجه الأجهزة الحكومية لعديد دول العالم أزمات متعددة نظير تبنيها للمنوذج البيروقراطي في تسيير شؤونها الإدارية، هذه السلبيات أدت إلى إنتشار الفساد والمحسوبية واستغلال النفوذ وغيرها من المظاهر التي أصبحت جزءا أساسيا ومظهرا يميز جميع أشكال المؤسسات الحكومية لهذه الدول، وعليه فإن هذه الدراسة تتناول إبراز دور تطبيق الإدارة الإلكترونية كآلية تقنية حديثة في التغلب على هذه المظاهر السلبية داخل الأجهزة الإدارية الحكومية بهدف الخروج بها نحو تحقيق الشفافية والنزاهة في التسيير . حيث خلصت في النهاية إلى ضرورة تبني هذا النموذج الذي يساهم في القضاء على أزمة التسيير البيروقراطي. The government agencies of many countries of the world are facing multiple crises because of their adoption of the bureaucratic model in the conduct of their administrative affairs .These disadvantages have led to the spread of corruption, cronyism, the exploitation of influence and other manifestations that have become an essential part of all forms of governmental institutions of these countries. This study, therefore, highlights the role of the application of electronic administration as a modern technical mechanism in overcoming these negative manifestations within government administrative organs with a view to bringing them towards transparency and integrity in the conduct of the administration. Ultimately, I concluded that this model, which contributes to the elimination of the bureaucratic crisis, should be adopted.
E-administration Between The Requirements Of Transparency And The Problematic Elimination Of Bureaucracy In Governmental Institutions
مجلد 12 العدد 02
Keywords: لإدارة الإلكترونية؛ البيروقراطية؛ الشفافية؛; e-administration; bureaucracy;transparency